1999
DOI: 10.1038/sj.bjp.0702976
|View full text |Cite
|
Sign up to set email alerts
|

An anti‐platelet agent, OPC‐29030, inhibits translocation of 12‐lipoxygenase and 12‐hydroxyeicosatetraenoic acid production in human platelets

Abstract: In human platelets, arachidonic acid is mainly metabolized by the two enzyme systems; cyclo‐oxygenase and 12‐lipoxygenase. Cyclo‐oxygenase produces prostaglandin H2 which is further converted to thromboxane B2. 12‐Lipoxygenase synthesizes 12(S)‐hydroperoxyeicosatetraenoic acid which is reduced to 12(S)‐hydroxyeicosatetraenoic acid (12(S)‐HETE). An anti‐platelet compound, OPC‐29030, dose‐dependently inhibited 12(S)‐HETE production with an IC50 of 0.06±0.01 μM, but not synthesis of thromboxane B2 in human platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 25 publications
(24 reference statements)
0
19
0
1
Order By: Relevance
“…This compound was first found to inhibit translocation of 5-lipoxygenase (24) but later shown to inhibit translocation of other lipoxygenases without affecting the enzyme activity per se (25). As shown in Fig.…”
Section: Membrane Translocation Of 12/15-lipoxygenase By Ldl-12/mentioning
confidence: 90%
See 1 more Smart Citation
“…This compound was first found to inhibit translocation of 5-lipoxygenase (24) but later shown to inhibit translocation of other lipoxygenases without affecting the enzyme activity per se (25). As shown in Fig.…”
Section: Membrane Translocation Of 12/15-lipoxygenase By Ldl-12/mentioning
confidence: 90%
“…In 5-lipoxygenase, the N-terminal C2-like domain is demonstrated to be a calciumdependent membrane-targeting domain without requirement of any special docking protein (33). We have reported that 12-lipoxygenase in human platelets is activated by membrane translocation when stimulated by collagen or thrombin and that a translocation inhibitor of 5-lipoxygenase, L655238, inhibits production of 12-HETE from platelets without affecting the enzyme activity (25). The results clearly indicate that L655238 is not a 5-lipoxygenase-specific inhibitor but a general translocation inhibitor of lipoxygenases.…”
Section: Membrane Translocation Of 12/15-lipoxygenase By Ldl-12/mentioning
confidence: 98%
“…50,51 In agreement, a translocation inhibitor, L-655238, substantially inhibited GPVI-dependent 12-H(P)ETE synthesis similar to previous reports using collagen ( Figure 2D). 15 However, Ca 2ϩ mobilization is not in itself sufficient for p12-LOX activation, because a concentration of thrombin that did not cause 12-H(P)ETE synthesis caused significantly greater Ca 2ϩ mobilization than collagen ( Figure 2C). GPVI stimulation of 12-H(P)ETE generation was inhibited by PP2, staurosporine, and wortmannin, implicating srctyrosine kinases and PI3-kinase in p12-LOX activation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular distribution of 12-LO activity varies between different cells, ranging from a predominant cytosolic 20 localization to a preferential localization in membranes. 21 In human platelets, most 22 but not all 23 investigators have observed a predominant (65%) localization of 12-LO activity and protein in the cytosolic fraction. 12(S)-HETE has also been shown to participate in the regulation of platelet function such as aggregation and P-selectin expression.…”
Section: Discussionmentioning
confidence: 99%